Storm Clouds and Rainbows: Visual Metaphors of Parents of Transgender Children in Aotearoa (New Zealand) - de Bres J; Morrison-Young I (Taylor and Francis Group, 2023)
This article explores the discourses parents adopt to support their transgender children in Aotearoa (New Zealand). Previous research with parents is limited by its focus on trauma rather than resistance and its lack of attention to intersectional experiences. To investigate how parents resist gender-based oppression, we use the method of reflective drawing, asking twenty parents of diverse social and cultural backgrounds to draw their experience of parenting a transgender child and discuss this in interview. We identified eight visual metaphors of storm clouds and rainbows, a maze, family portraits, blank space, standing side-by-side, hearts, arches, and question marks. These represent parent discourses of family resilience, personal transformation, shifting gender ideologies, depathologisation, child-led parenting, unconditional love, protection, and uncertainty about their child’s future. The parents’ discourses serve several interests: enabling them to focus on the hope of overcoming adversity, foreground the positive aspects of raising a transgender child, justify their gender-affirming approach, reframe their family gender ideologies, normalize their child’s experience, deflect stigma from their child and themselves, construct themselves as good parents, draw strength from solidarity, and express incertitude about what lies ahead. These provide parents with a means of enacting discursive resistance, with potential for driving broader social change.
Keywords: Transgender children; parenting; discourse; drawing; metaphor